The synthetic cannabinoid JWH-018 modulates Saccharomyces cerevisiae energetic metabolism. Issue 5 (20th June 2019) - Ferreira, Carla; Couceiro, Joana; Família, Carlos; Jardim, Carolina; Antas, Pedro; Santos, Cláudia N; Outeiro, Tiago F; Tenreiro, Sandra; Quintas, Alexandre
ABSTRACT: Synthetic cannabinoids are a group of novel psychoactive substances with similar properties to Δ 9 -THC. Among the vast number of synthetic cannabinoids, designed to be tested in clinical trials, JWH-018 was the first novel psychoactive substance found in the recreational drug marketplace. The consumption of JWH-018 shows typical effects of CB1 agonists including sedation, cognitive dysfunction, tachycardia, postural hypotension, dry mouth, ataxia and psychotropic effects, but appeared to be more potent than Δ 9 -THC. However, studies on human cells have shown that JWH-018 toxicity depends on the cellular line used. Despite these studies, the underlying molecular mechanisms to JWH-018 action has not been clarified yet. To understand the impact of JWH-018 at molecular and cellular level, we used Saccharomyces cerevisiae as a model. The results showed an increase in yeast growth rate in the presence of this synthetic cannabinoid due to an enhancement in the glycolytic flux at expense of a decrease in pentose phosphate pathway, judging by 2D-Gel proteomic analysis, qRT-PCR experiments and ATP measurements. Overall, our results provide insights into molecular mechanisms of JWH-018 action, also indicating that Saccharomyces cerevisiae is a good model to study synthetic cannabinoids. Abstract : Present work implemented S. cerevisiae model to understand the impact of JWH-018 on molecular and cellular levels. The results showed that JWH-018 improves cell fitness by modulating glycolytic levels.